Evaluation of Residents’ Comfort in High-Rise Residential Buildings in Dubai, United Arab Emirates - Jung, Chuloh; Awad, Jihad; Al Qassimi, Nahla (Frontiers in Built Environment, 2021)
The global record of 1,700 % urban footprint growth in only 38 years made Dubai one of the fastest growing cities in the world. The density of metropolis population is approximately 762.6 individuals/km2 and high-rise residential building in Dubai have reached 581,166 units (79%) in 2020 and become a common residential type. The objective of this paper is to provide basic data for the design of high-rise residential buildings in the future by evaluating the health of the residents of high-rise residential buildings in Dubai. As a methodology, Todai Health Index, a structured health assessment tool, was used for high-rise residents’ survey. For the analysis, the health evaluation data from residents were used as the dependent variable, and the number of living floors as the architectural characteristic and the indoor temperature and humidity condition as the residential environments were analyzed as the independent variable. The result had shown that residence floor is irrelevant to overall health, changes in health status compared to one year ago, occurrence of daily diseases health evaluation by Todai Health Index. It was statistically proven that the thermal environment has a significant correlation with the residence floor but the effect of the thermal environment on health was not strong. However, the humidity environment has a very strong relationship with the health of residents. Humidity environment has a very close relationship not only with the occurrence of daily diseases of residents, but also with the health evaluation analyzed by the Todai Health Index. There is a significant relationship between humidity environment and both physical and mental health. It was analyzed that a slightly humid condition had a positive effect on health.